PENGARUH MEDIA LOOSE PART TERHADAP MINAT BELAJAR ANAK USIA DINI - Saanih; Imamah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Agama Islam Universitas Nahdlatul Ulama Purwokerto, 2024)
This study aims to analyze the influence of loose part media on the learning interest of Group B children at TK Nasional Plus Tunas Global. Learning interest is a crucial factor in the success of early childhood education, and engaging learning media can enhance children's motivation to learn. Loose part media, consisting of manipulable materials, provides children with opportunities to explore and create. The research employs a quantitative approach with a quasi-experimental design. The sample involves two groups of children, with one group receiving the loose part media intervention and the other serving as a control. Observation instruments are used to measure learning interest indicators such as curiosity, interest, attention, involvement, and persistence. The results indicate that the use of loose part media has a significant positive effect on children's learning interest. Children who engaged with loose part media showed higher increases in learning interest compared to the control group. These findings affirm the importance of innovative and interactive teaching approaches in early childhood education.The study provides practical implications for educators and parents in selecting and using appropriate learning media to support optimal growth and development in young children. It also offers a foundation for further research on the impact of loose part media on other aspects of child development